The impact of correctional officer gender on prison suicide - TaLisa J. Carter; Tanya N. Whittle (BMC, 2023)
Abstract Correctional officers are critical members of the prison community. However, scholarship rarely considers how correctional officers contribute to prison outcomes instead largely focusing on importation (individual) and deprivation (organizational) factors related to the incarcerated population. This is also true regarding how scholars and practitioners approach suicide committed by incarcerated people, one of the leading causes of death in US carceral institutions. Using quantitative data from confinement facilities across the United States, this study answers the research question: What is the relationship between prison suicide rates and correctional officer gender? Results show that deprivation factors (variables related to the carceral environment) influence prison suicide. Additionally, gender diversity among correctional officers reduces the rate of prison suicide. Implications for future research and practice and limitations of the study are also discussed.